2019
DOI: 10.1017/s1041610219001704
|View full text |Cite
|
Sign up to set email alerts
|

Assistive technology designed to support self-management of people with dementia: user involvement, dissemination, and adoption. A scoping review

Abstract: Background: Assistive technology is advocated as a key solution to the need for support among people living with dementia. There is growing awareness of the benefits of user involvement in the design and test of these technologies and the need to identifying applicable and effective methods for implementation. The aim of this review was to explore and synthesize research addressing assistive technology designed to be used by people with dementia for self-management. Further research aims were to explore if and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…A recent systematic review by Sriram et al explored the use of IAT by caregivers of those with dementia and the impact of these technologies on carer's lives with the recommendation for a standard and person-centered system be developed (25). A scoping review by Øksnebjerg et al focused on the need for high-quality research into essential aspects of delivering applicable, effective, and sustainable assistive technology to support self-management of people with dementia suggesting the need for evidence-based methods to promote and qualify user involvement, dissemination, and adoption (26). For the most part, this current research articulates concerns for ethics issues such as privacy, security and consent have occurred ex post of the implementation or in the process of use.…”
Section: Ethics and Values For Dementia Care: The Need To Be Proactivmentioning
confidence: 99%
“…A recent systematic review by Sriram et al explored the use of IAT by caregivers of those with dementia and the impact of these technologies on carer's lives with the recommendation for a standard and person-centered system be developed (25). A scoping review by Øksnebjerg et al focused on the need for high-quality research into essential aspects of delivering applicable, effective, and sustainable assistive technology to support self-management of people with dementia suggesting the need for evidence-based methods to promote and qualify user involvement, dissemination, and adoption (26). For the most part, this current research articulates concerns for ethics issues such as privacy, security and consent have occurred ex post of the implementation or in the process of use.…”
Section: Ethics and Values For Dementia Care: The Need To Be Proactivmentioning
confidence: 99%
“…Research supports the incorporation of technology with dementia patients because it plays a role in preventing their cognitive and physical decline. Technological intervention could further propose solutions to the challenges and barriers that limit care in dementia patients [4].…”
Section: Rationalementioning
confidence: 99%
“…These are valuable insights supporting the development of classifier selection models that guide practitioners to choose the best algorithm in a particular application context. In this respect, Øksnebjerg et al [25] presented a review to investigate user involvement, dissemination, and adoption of assistive technology by PwD. The papers included in the review were eleven papers from eight studies.…”
Section: A Background On Assistive Technology Solutions (Ats) For Pwdmentioning
confidence: 99%
“…The papers included in the review were eleven papers from eight studies. Øksnebjerg et al [25] reported that none of the studies considered dissemination, user involvement varied from extensive to none, and methods for adoption also varied and only targeted prototype testing. Some of the adoption methods reported from the reviewed papers were individual introduction, individualized program, audio-based guidance included in an app, a training session and manual for caregivers, and an individualized training session for both participant and caregiver.…”
Section: A Background On Assistive Technology Solutions (Ats) For Pwdmentioning
confidence: 99%